Sport and its female fans - Toffoletti, Kim.; Mewett, Peter. (Routledge research in sport, culture and society ;, 2012)
"Why do women follow sports? How do they participate from the sidelines and what is the significance of this contribution? What can female fandom tell us about gender relations in sport? This book explores these and related questions by bringing together the varied strands of research being conducted internationally across the social sciences and humanities on this emerging and topical field.While sports spectatorship is a popular and well-respected site of analysis, no book-length, scholarly contribution documents womens experiences of sports fandom. For this reason, there is an obvious need for a book that offers researchers, students and non-professional readers an authoritative introduction to womens modes of sport support. Sport and Its Female Fans will be a landmark contribution in the field of sport research and in studies of sports fandom, making an original contribution to the growing, yet under-researched, area of female sports spectators"--